Membangun bangsa yang inklusif: Toleransi, pluralisme, dan multikulturalisme dalam pendidikan Indonesia - Nasywaa, Naila Afiya Ramadhani (Maliki Interdisciplinary Journal, 2026)
Indonesia is a country with extraordinary diversity in terms of ethnicity, religion, race, and culture. This diversiy has given rise to tolerance, pluralism, and multiculturalism as vital pillars of national life. This article examines the philosophical foundations of these three concepts in the Indonesian context, edentifies models of their application in education, and explores the contemporary challenges faced. Using a qualitative approach, along with literature revie and document analysis methods, this study finds that the values of tolerance are deeply rooted in local Indonesian cultural history. The development of multicultural personality in students can be achieved through three multicultural psychological approaches: the individual, relational, and policy ideological approaches. This study concludes that the internalization of Pancasila, the strengthening of social capital, and the revitalization of tolerance based on local wisdom are key to maintaining harmony amidst diversity in the face of the challenges of radicalism the politicization of identity.